Prospect.4 the lotus in spite of the swamp : a project of Prospect New Orleans - Schoonmaker, Trevor (DelMonico Books, Prestel, 2017)
Now in its fourth iteration, Prospect New Orleans draws its inspiration from the city itself, a place of graceful beauty that thrives in adverse conditions. By positioning itself in the city of New Orleans, the Prospect triennial aims to echo the city's history of cross-cultural fertilization. From Creole culture to jazz, in waves of migration and colonization, and as the American South's largest port, New Orleans is truly a cultural and historic nexus. 'Prospect.4' plumbs New Orleans's richly hybrid character to offer a diverse and exhilarating panoply of new and exciting art. Exhibition: New Orleans (various venues), United States (11.11.2017-25.02.2018)
Keywords: Geschichte 2015-2017; Kunst; New Orleans, La.; Ausstellungskatalog -- 11.11.2017-25.02.2018 -- New Orleans, La.